Current approaches to waste polymer utilization and minimization: a review. Issue 1 (27th August 2018) - Okan, Meltem; Aydin, Halil Murat; Barsbay, Murat
Abstract: The mass production of polymer products, in particular plastics, and their widespread use depending on the inherent advantages they have, make these materials ironically a threat to life on Earth. Polymer recycling is being considered as one of the most widely accepted remedies to the threat of growing amounts of plastic waste by both the public and scientists. In practice, recycling is associated with many difficulties, such as problems related to separation, sorting and cleaning operations, lack of fiscal subsidies, instability of selective garbage separation programs, high transport and electricity costs, etc. Still, a large section of society and the authorities agree on the necessity and importance of recycling to protect the environment, and natural habitats and resources for future generations in a balanced manner to conserve raw materials, and to reduce energy consumption, municipal solid waste production and greenhouse gas emission. The recycling effort is almost endless in itself and includes a variety of approaches such as refurbishing, mechanically reshaping, chemically treating, thermally utilizing, etc. Some novel approaches such as application in carbon capture or synthesis of carbon nanostructures from the plastic waste are among the new process technologies of recycling. From traditional and promising polymer waste utilization approaches, this review will highlight sustainable methods to reduce impacts of plastic waste on the environment. © 2018 Society of Chemical Industry